The Fulfilment of Right to Education for Persons with Disabilities: A Challenge in a Border Area - Yahya Ahmad Zein; Arif Rohman; Dewi Nurvianti (Sriwijaya Law Review, 2020)
This study discusses the right to education policy for Persons With Disabilities (PwDs) In Border Area of Nunukan-Indonesia. This research aims to find out whether the legal regulation on human rights for with disabilities provided by the Indonesian government is appropriate or not and to find out whether the government of Nunukan District also provided some policies in handling a person with disabilities, in particular, their right to education. This research used a normative legal method, which complemented with field research. As a result, in order to fulfil human rights for PwDs, the Indonesian government was stipulated plenty of national laws, namely National Education System Law, the Protection of Children Law, and individually regulated by Law No. 8 of 2016 on Persons with Disabilities. Also, the most crucial factor is that the Nunukan District has not been set up the local regulation pertaining to PwDs. Only several policies are stipulated to overcome the right to education problems, but it does not enough to ensure the correct implementation of this right in the field.